Impact of unemployment by sex and marriage rate on fertility decline: Estimates for Turkey and Greece using CCR model - Goran Miladinov (Moscow State University, Faculty of Economics, 2021)
﻿ The article analyses the effect of unemployment by sex and marriage rate on fertility changes in Greece and Turkey. The empirical part of the study is based on annual time series data retrieved from the World Bank and National Statistical Offices of Turkey and Greece for 1991–2019. Canonical Cointegrating Regression model is applied for the two countries separately, allowing to quantify the effects of the determinants (crude marriage rate and unemployment rate by sex) on the variation of fertility rate. CCR models show these determinants to be the most significant factors of fertility dynamics in both countries. The results from Engle-Granger and the Phillips-Ouliaris tau (t-statistics) tests confirm the cointegration, i.e., long-term relationship between the variables only for Turkey’s CCR model. However, it was found that in Greece, female unemployment impacts fertility rate negatively and male unemployment has a positive effect on fertility rate; for Turkey modelling shows the opposite relationship. The results of the study suggest that economic uncertainties might be one of the factors contributing to fertility decline in these countries, long-term or in the coming years.